Metode Vikor dalam Meningkatkan Kualitas Pembelajaran Terhadap Pemilihan Studi Club - Junaidi (SEULANGA SYSTEM PUBLISHER, 2022)
Club studies are more non-formal learning methods and emphasize the participation of members/participants. In club studies, students get more roles than in class lectures, so club studies can be used as a companion method to increase student insight. Club studies are also one of the alternative learning methods designed to improve student competence by emphasizing the active participation of students. By participating in the study club, students have the ability to increase student scores compared to those who do not participate in the study club, so there is a difference between students who take part in the study club and those who do not take part in the study club. Student competence is very necessary, especially in the era of global competition. To find student talent in determining the selection of club studies as an alternative method of learning level in order to improve student competence and improve the quality of learning with the best graduates. Based on the analysis of improving the quality of learning in students against the selection of club studies with several criteria that can be taken from the students themselves, the assessment consists of the value of supporting courses, attendance values ​​of supporting courses, practical test scores and interests. From the various criteria that students have, from this it can provide a determination in the selection of club studies according to the results of the criteria values ​​owned by students..